Internationalization of Higher Education: A Case Study on Media Utilization, Policies Consistency and Stakeholders’ Insights in Indonesia - Nurhaeni, Ismi Dwi Astuti; Anggreni, Likha Sari; Kusumawati, Noni Srijati; Permitasari, Desti; Putri, Intan Sani (Research and Development Agency Ministry of Home Affairs, 2021)
The research discusses media utilization and contents for supporting the internationalization, the consistency of internationalization policies at the macro-level (Ministry), mezzo-level (Directorate General), and micro-level (Sebelas Maret University or known as UNS), and the stakeholders' insights of the internationalization of Higher Education. The data were obtained through in-depth interviews and documentation, and a descriptive-qualitative analysis technique was used. The results showed that UNS utilized various media to support internationalization, namely visual media, auditory media, audiovisual media, and other new media. Media contents include academic information, international research collaboration, and intercultural activities. Policy consistency from macro to micro levels took place only at the activity level, whereas there is no consistency in the mission, strategies, policies, and programs. The stakeholders' insights varied from understanding internationalization entirely as a goal, strategies, activities, media, and intra-cultural dimension standardized at the world level until the internationalization dimension. The implication of this research is the need to harmonize policies at all levels of the organization. Besides, the content of the media should be adjusted to the indicators of internationalization.